Tackling Sectarianism in Scotland. Issue 3 (August 2015) - Rosie, Michael; Clegg, Cecelia; Galloway, Ian; Lynch, Margaret; Morrow, Duncan
<x content-type="archive" xml:space="preserve">Abstract</x> The Advisory Group on Tackling Sectarianism in Scotland (AGoTS) was established in August 2012 to provide Scottish Ministers with impartial advice on how to develop and assess work to tackle sectarianism in Scotland. Key to the Group's work was understanding the forms that sectarianism may (or may not) take in contemporary Scotland, and how best to address these. This article sets out an overview of the Group, as well as outlining the key contours of this Special Issue of Scottish Affairs.